PENGARUH PEMBERIAN PUPUK ORGANIK TERHADAP PERTUMBUHAN BEBERAPA BENIH ASAL KLON KAKAO (Theobroma cacao L.) DI PEMBIBITAN - Hadriman Khair; Hasmawi Hasyim; Ridho Ardinata (AGRIUM: Jurnal Ilmu Pertanian, 2012)
This study aims to determine the growth response of some kind of clone of cocoa ( Theobroma cacao L. ) with an organic fertilizer in a polybag with using randomized block design (RBD ) factorial with 2 factors studied , namely : The first factor is Organic Fertilizer ( O ) divided into 3 levels ie O0 = Without Giving , O1 = Amazing Bio Fertilizer Growth ( ABG ) and O2 = Fertilizer Super Bionic , and the second factor varieties Cocoa ( K ) is divided into three types namely TSH K1 = 858 , K2 = 70 and K3 = RCC PA 300 . While the parameters measured were plant height ( cm ) , number of leaves ( blade ) , stem diameter ( mm ) , leaf area ( cm ) , root fresh weight ( g ) , stem fresh weight ( g ) , root dry weight ( g ) , stem dry weight ( g ) and root volume ( cc ) . The results showed that the use of organic fertilizers provide a significant effect on the parameters of plant height , leaf number , stem diameter , leaf area , stem fresh weight , and root volume and provide no real influence on the parameters of the wet weight of the rod . Treatment varieties only significant effect on plant height parameters , and no real influence on the other parameters .While the interaction of treatment showed a marked influence on the parameters for a high cocoa seedlings and other parameters showed no real difference.Key wordas : organic fertilizer, growth, cocoa